Policy Implementation of Integrated Poverty Alleviation Program-Village-based Surgery (PTPK-BBK) (Case Study in Fishermen Community in Bantaya Village, Parigi Sub-district, Parigi Moutong Regency, Central Sulawesi Province) - Susanto Susanto; Darsono Wisadirana; Sholih Muadi (Sekolah Pascasarjana Universitas Brawijaya, 2017)
The problem of poverty is a crucial issue in Indonesia; one of the issues is in Bantaya village, Parigi Sub-district, Parigi Moutong Regency. Therefore, it needs the poverty alleviation program, in this case Integrated Poverty Alleviation Program-Village-based Surgery (PTPK-BBK). The type of research is a qualitative descriptive, in which data collection is conducted by interviews with the key informants and data analysis is conducted via triangulation. The research results are: (1) the implementation of PTPK-BBK program in Bantaya village has been done in accordance with the procedure. Nevertheless, the PTPK-BBK program gives less significant impact on the life of fishermen. It is due to lack of post-implementation of evaluation and monitoring program; (2) the supporting factor of PTPK-BBK is the facilitators who carry out their duties maximally, meanwhile the inhibiting factor is coming from the community itself or within the program such as the natural disaster, middlemen, and low evaluation system.Â